Navigating the digital shift: EFL lecturers’ perceptions and pedagogical barriers in LMS-based blended learning at a Vietnamese university - Ha, Pham Thi Xuan (Edelweiss Applied Science and Technology, 2026)
As digital transformation reshapes higher education, this study investigates English as a Foreign Language (EFL) lecturers’ perceptions of Learning Management System (LMS) integration within blended learning frameworks. Employing an explanatory sequential mixed-methods design, the research gathered survey data from 18 lecturers at a Vietnamese university, complemented by follow-up semi-structured interviews with six participants. Findings reveal a predominantly positive stance toward LMS integration (M = 3.94); however, a notable disparity exists in lecturers’ confidence concerning blended course design and implementation (M = 3.12). While participants recognized advantages such as pedagogical flexibility and increased learner autonomy, they identified substantial challenges, including inadequate pedagogical guidance, difficulties in tracking student engagement, and the heavy workload inherent in digital content development. Consequently, the study concludes that institutional support must shift from basic technical instruction toward developing comprehensive digital pedagogical competencies. The findings imply that establishing professional learning communities is essential for sustainable digital integration. Although focused on a specific institutional context, this research offers valuable implications for EFL environments undergoing similar pedagogical shifts.